Identification of inorganic compounds in eggshell as a dental remineralization material - Asmawati Asmawati (Journal of Dentomaxillofacial Science, 2017)
Objective: Many patients suffer from sensitive teeth after bleaching that can cause demineralization of enamel and widening of dentinal tubules. Hence, researchers are looking for natural ingredients for enamel remineralization material include chicken egg shells because it contain calcium carbonate that can restore lost inorganic compounds. This study aimed to identify inorganic compound in eggshell as dental remineralization agent.Materials and methods:This study was an experimental laboratory with with post test only control group design. The research sample was five maxillary central incisor that has been applied with 35% hydrogen peroxide bleaching material in different time range 1 hour, 1 hour 30 minutes, 2 hours, 2 hours 30 minutes and 3 hours. Then, samples were applied with chicken egg shells gel for 14 consecutive days. Identification of inorganic compound was analyzed using Energy Dispersive X-ray Spectroscopy (EDS).Results: The application of chicken egg shells gel do not cause a significant difference in the composition of enamel compound between control group and treatment group.Conclusions: There is an increasing number of inorganic compounds in samples that had been applied with eggshell gel such as calcium, phosphorus, magnesium, chlorine, oxygen, and aluminium.